Generation of Immunodeficient Rats With Rag1 and Il2rg Gene Deletions and Human Tissue Grafting Models. Issue 8 (August 2018) - Ménoret, Séverine; Ouisse, Laure-Hélène; Tesson, Laurent; Delbos, Frédéric; Garnier, Delphine; Remy, Séverine; Usal, Claire; Concordet, Jean-Paul; Giovannangeli, Carine; Chenouard, Vanessa; Brusselle, Lucas; Merieau, Emmanuel; et al.
Abstract : Background: Immunodeficient mice are invaluable tools to analyze the long-term effects of potentially immunogenic molecules in the absence of adaptive immune responses. Nevertheless, there are models and experimental situations that would beneficiate of larger immunodeficient recipients. Rats are ideally suited to perform experiments in which larger size is needed and are still a small animal model suitable for rodent facilities. Additionally, rats reproduce certain human diseases better than mice, such as ankylosing spondylitis and Duchenne disease, and these disease models would greatly benefit from immunodeficient rats to test different immunogenic treatments. Methods: We describe the generation of Il2rg -deficient rats and their crossing with previously described Rag1 -deficient rats to generate double-mutant RRG animals. Results: As compared with Rag1 -deficient rats, Il2rg -deficient rats were more immunodeficient because they partially lacked not only T and B cells but also NK cells. RRG animals showed a more profound immunossuppressed phenotype because they displayed undetectable levels of T, B, and NK cells. Similarly, all immunoglobulin isotypes in sera were decreased in Rag1- or Il2rg -deficient rats and undetectable in Rats Rag1 and Il2rg (RRG) animals. Rag1- or Il2rg -deficient rats rejected allogeneic skin transplants and human tumors, whereas animals not only accepted allogeneic rat skin but also xenogeneic human tumors, skin, and hepatocytes. Immune humanization of RRG animals was unsuccessful. Conclusions: Thus, immunodeficient RRG animals are useful recipients for long-term studies in which immune responses could be an obstacle, including tissue humanization of different tissues. Abstract : The successful generation of double mutant Il2rg- and Rag1-deficient (RRG) rats that accept allogeneic rat skin and xenogeneic human tumors, skin and hepatocytes. However immune humanization of RRG rats was unsuccessful, pointing to the need for additional genetic modifications. Supplemental digital content is available in the text.